STRUKTUR WACANA RITUAL (Studi Kasus Ritual Selametan di Pesarean Gunung Kawi, Malang, Jawa Timur) - Nuryani Nuryani (Sunan Kalijaga State Islamic University Yogyakarta, 2013)
Rituals of selametan (celebrations of thanksgiving and / or to ask the blessingsand favours from the God, gods, or spirits) can be found at Pesarean Gunung Kawi, Malang, East Java. In this place, the ritual has some purposes. These can be known from the discourse that is spoken by modin or the leader of the ritual ceremony. The objective of this study is to describe the structure of the speech discourse in ritual of selametan. Data recordings which are obtained in the form of implementation of the ritual were transcribed. Based on the research and analysis, some results can be concluded. The views of the structure of language or the speech discourse, in selametan ritual are composed of invitation, solicitation/expectations, and statement sentences. The invitations appear in the early discourse, expectations appear in all parts of the discourse, while statements also appear in each section.